2023
DOI: 10.1371/journal.pone.0282499
|View full text |Cite
|
Sign up to set email alerts
|

Detection of azole-resistant Aspergillus fumigatus in the environment from air, plant debris, compost, and soil

Abstract: Aspergillus fumigatus is a ubiquitous fungus, a saprophyte of plants, and an opportunistic pathogen of humans. Azole fungicides are used in agriculture to control plant pathogens, and azoles are also used as a first line of treatment for aspergillosis. The continued exposure of A. fumigatus to azoles in the environment has likely led to azole resistance in the clinic where infections result in high levels of mortality. Pan-azole resistance in environmental isolates is most often associated with tandem-repeat (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
0
0
Order By: Relevance
“…fumigatus complex species as well as further delineating the role of membrane transporter protein gene and non-cyp51A mutations such as cholesterol import and HapE mutations [144][145][146]. Targeted sequencing with pre-amplification of tandem repeat regions can be performed, but the utility of these methods is unclear when non-cyp51A mediated triazole-resistant clinical isolates ranges from 15 to 60% [146,147].…”
Section: Aspergillusmentioning
confidence: 99%
“…fumigatus complex species as well as further delineating the role of membrane transporter protein gene and non-cyp51A mutations such as cholesterol import and HapE mutations [144][145][146]. Targeted sequencing with pre-amplification of tandem repeat regions can be performed, but the utility of these methods is unclear when non-cyp51A mediated triazole-resistant clinical isolates ranges from 15 to 60% [146,147].…”
Section: Aspergillusmentioning
confidence: 99%
“… 9 Since then, it has been demonstrated that the majority of cases of azole-resistant disease arise when an azole-naive patient is infected with an azole-resistant strain from the environment, which is frequently found in air and soil. 8–10 , 16–18 …”
Section: Introductionmentioning
confidence: 99%
“…Since all azoles target the enzyme lanosterol-14-alpha-demethylase ( cyp 51), which inhibits the biosynthesis of ergosterol, cross-resistance is seen between the medical and agricultural azoles. 8 , 24 , 25 Aspergillus fumigatus has two cyp 51 isoforms, namely c yp 51A and cyp 51B. Most azole-resistant strains display mutations in the cyp 51A gene, although other resistance mechanisms have been described.…”
Section: Introductionmentioning
confidence: 99%